Water Quality Black Water River Pekanbaru in terms of Physics-Chemistry and Phytoplankton Communities - Dedy Muharwin Lubis; Nur El Fajri; Eni Sumiarsih (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study was conducted in April 2016 in the Black Water RiverPekanbaru in Riau. This study aims to determine the water quality of the BlackWater River Pekanbaru in terms of aspects of physics, chemistry andphytoplankton community. Samples were taken at four stations, namely upstream,middle, downstream rivers, and estuaries. Time taking water samples performedtwice at each station began at 09.00-15.00 pm with an interval of one week.Based on the results of research in the Black Water River Pekanbaru foundfour types of phytoplankton are classified in three classes of Bacillariophyceae(1jenis), Chlorophyceae (one type), and Cyanophyceae (2Jenis). Total abundanceof phytoplankton ranges from 225-1575 cells / L. The value of the diversity index(H ') ranged 0,6954- 0.8907, uniformity index (E) ranges from 0.1241 to 0.2679,and the dominance index (C) ranges from 0.6525 to 0.8205. Water qualityparameters in which the temperature can range from 27.67 - 29,330C, brightnessranges from 31.8 to 33.5 cm, pH 5, dissolved oxygen ranges from 4.96 to 6.73 mg/ L, nitrate ranged 0,1222- 0.6583 mg / L and phosphate ranging from 0.532 to0.8086 mg / L. Based on the results of this study concluded that the totalabundance of phytoplankton showed that Black Water River Pekanbaru classifiedinto waters with low fertility rate.Kata Kunci: Sungai Air Hitam, Kualitas Air, Indeks Kimia